Guided Anti-P2Y12 Therapy in Patients Undergoing PCI: Three Systematic Reviews with Meta-analyses of Randomized Controlled Trials with Homogeneous Design - Birocchi, Simone; Rocchetti, Matteo; Minardi, Alessandro; Podda, Gian Marco; Squizzato, Alessandro; Cattaneo, Marco (Thrombosis and haemostasis, 2024)
The value of guided therapy (GT) with anti-P2Y12 drugs in percutaneous coronary intervention (PCI) is unclear. Meta-analyses lumped together randomized controlled trials (RCTs) with heterogeneous designs, comparing either genotype-GT or platelet function test (PFT)-GT with unguided therapy. Some meta-analysis also included RCTs that did not explore GT, but included the effects of switching patients with high on-treatment platelet reactivity (HTPR) to alternative therapies (HTPR-Therapy). We performed three distinct systematic reviews/meta-analyses, each exploring only RCTs with homogeneous design. MEDLINE, Embase, and Central databases were searched for RCTs testing genotype-GT, PFT-GT, or HTPR-Therapy in PCI-treated patients, through October 1, 2022. Two reviewers extracted the data. Risk ratios (RRs) (95% confidence intervals) were calculated. Primary outcomes were major bleedings (MBs) and major adverse cardiovascular events (MACE). In seven genotype-GT RCTs, RRs were: MB, 1.06 (0.73-1.54; = 0.76); MACE, 0.65 (0.47-0.91; = 0.01), but significant risk reduction was observed in RCTs performed in China (0.30, 0.16-0.54; < 0.0001) and not elsewhere (0.75, 0.48-1.18; = 0.21). In six PFT-GT RCTs, RRs were: MB, 0.91 (0.64-1.28, = 0.58); MACE, 0.82 (0.56-1.19; = 0.30): 0.62 (0.42-0.93; = 0.02) in China, 1.08 (0.82-1.41; = 0.53) elsewhere. In eight HTPR-Therapy RCTs, RRs were: MB, 0.71 (0.41-1.23; = 0.22); MACE, 0.57 (0.44-0.75; < 0.0001): 0.56 (0.43-0.74, < 0.0001) in China, 0.58 (0.27-1.23, = 0.16) elsewhere. No GT strategy affected MB. Overall, genotype-GT but not PFT-GT reduced MACE. However, genotype-GT and PFT-GT reduced MACE in China, but not elsewhere. PFT-GT performed poorly compared to HTPR-Therapy, likely due to inaccurate identification of HTPR patients by PFT.